The Social Politics of Medieval Diplomacy : Anglo-German Relations (1066-1307). (University of Michigan Press, 2009)
Late nineteenth- and twentieth-century political and intellectual boundaries have heavily influenced our views of medieval Germany. Historians have looked back to the Middle Ages for the origins of modern European political crises. They concluded that while England and France built nation-states during the medieval era, Germany--lacking a unified nation-state--remained uniquely backward and undeveloped. Employing a comparative social history, Huffman reassesses traditional national historiographies of medieval diplomacy and political life. Germany is integrated into Anglo-French notions of western Europe and shown to be both an integral player in western European political history as well as a political community that was as fully developed as those of medieval England or France. The Social Politics of Medieval Diplomacy offers a study of the social dynamics of relations between political communities. In particular, the Anglo-French political communities do not appear as state and constitution builders, while the German political community is not as a state and constitution destroyer. The book concludes by encouraging medievalists to integrate the German kingdom into their intellectual constructs of medieval Europe. This book is an essential history of medieval Germany. It bridges the gaps between Anglo-French and German scholarship and political and social history. Joseph Huffman makes available German-language scholarship. Both English and German history is integrated in an accessible and interesting way. The historiographical implications of this study will be far-reaching. Joseph P. Huffman is Associate Professor of History and Political Science, Messiah College.